Changing Saudi Arabia art, culture, and society in the Kingdom - Foley, Sean 1974- (Boulder Lynne Rienner Publishers, 2019)
Explores the role of Saudi Arabia's arts movement in promoting progressive social reform in the kingdom.
Creating change in Saudi Arabia -- The modern Saudi visual arts movement -- The emerging comedy scene -- Media companies and filmmakers -- Shaping the future.
Includes bibliographical references (pages 189-209) and index.
Keywords: Art -- Saudi Arabia; Arts -- Saudi Arabia; Arts and society -- Saudi Arabia; Mass media -- Saudi Arabia; Motion pictures -- Saudi Arabia; Stand-up comedy -- Saudi Arabia